2013
DOI: 10.1182/blood-2012-05-431452
|View full text |Cite
|
Sign up to set email alerts
|

Delayed development of chronic lymphocytic leukemia in the absence of macrophage migration inhibitory factor

Abstract: IntroductionChronic lymphocytic leukemia (CLL) is a clonal B-cell disorder that is not curable by conventional chemoimmunotherapies. The leukemic transformation may be initiated by specific genomic alterations (eg, del13q) that may cause the deletion of specific micro-RNA genes (eg, miR15 and miR16) and increase the resistance of B cells toward apoptosis. 1,2 Survival of CLL cells depends on a permissive microenvironment composed of cellular components, such as macrophages, T cells, or stromal follicular dendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 58 publications
4
74
1
Order By: Relevance
“…47 Interestingly, high levels of macrophage migration inhibitory factor have been detected in sera from CLL patients and lack or inhibition of this factor delays CLL development in the Eμ-TCL1 mouse model of the disease. 48 In keeping with our data, a phenotype resembling tumor-associated M2 macrophages has been recently proposed for NLC 49 as well as deregulation of genes involved in phagocytosis and inflammation for CLL-monocytes. 50 Intriguingly, acquisition of an M2 phenotype appears to be induced under the influence of malignant CLL cells as we demonstrated in normal monocytes, through IDO and c-MET upregulation.…”
Section: Discussionsupporting
confidence: 71%
“…47 Interestingly, high levels of macrophage migration inhibitory factor have been detected in sera from CLL patients and lack or inhibition of this factor delays CLL development in the Eμ-TCL1 mouse model of the disease. 48 In keeping with our data, a phenotype resembling tumor-associated M2 macrophages has been recently proposed for NLC 49 as well as deregulation of genes involved in phagocytosis and inflammation for CLL-monocytes. 50 Intriguingly, acquisition of an M2 phenotype appears to be induced under the influence of malignant CLL cells as we demonstrated in normal monocytes, through IDO and c-MET upregulation.…”
Section: Discussionsupporting
confidence: 71%
“…In addition to BAG6, other factors known to compromise NK cell function were also elevated in CLL patients including macrophage migration inhibitory factor 41 (supplemental Figure 4) and soluble ligands for NKG2D (MICA/B and ULBP2) (Figure 4). This is in line with a recent study that described a prognostic relevance for soluble ULBP2 level for the therapy-free survival of CLL patients.…”
Section: Discussionmentioning
confidence: 99%
“…86,87 Moreover, the potential role of the tumor microenvironment in signaling to malignant B cells through wingless-type MMTV integration site family (WNT) receptors 88 was addressed by genetically ablating the WNT receptor frizzled 6 (fzd6) in Em-TCL1 mice. The results suggested that dysregulated FZD6 expression modulates the disease course as it delayed but did not abrogate tumor growth.…”
Section: /2mentioning
confidence: 99%